PERBEDAAN TINGKAT INFLASI, NILAI TUKAR RUPIAH DAN SUKU BUNGA SEBELUM DAN SELAMA PANDEMI COVID 19 - Amalia Nur Chasanah; Sabtarini Kusumaningsih (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2021)
The Covid 19 pandemic that has hit the world has caused the economy to slow down. Many people have been affected by this pandemic, such as the number of layoffs and a reduction in working hours which resulted in a decrease in people’s income. This study aims to see differences in Indonesia’s macroeconomic conditions such as seen from the inflation rate, exchange rate and interest rate in conditions before the pandemic and during the covid 19 pandemic. The period used is January 2019 to February 2020 for conditions before the pandemic and March 202 to April 2021 for conditions during the pandemic. The mount of data is 28 months using the method of analysis of the independent sample difference test. The result of this study is that it has been proven that there are differences in the average rate of inflation, exchange rate and interest rates before the pandemic and during the pandemic.Keyword : inflation, exchange rate, interest rate